HUBUNGAN KUALITAS KEHIDUPAN KERJA DAN KINERJA KARYAWAN HOTEL BERBINTANG DI LOVINA BALI KETIKA LUMPUHNYA PARIWISATA - Marini, Ni Nyoman Nina; Sutrisna, I Putu Edi; Paragae, I Gusti Ayu Putu Novita Sari (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
Research on the correlation of the quality work life and employees' performance during the pandemic has not been carried out much. This study aimed at determining and analyzing the relationship between the quality of work life and the performance of employees at five-star hotels in the tourist area of Lovina Beach, Buleleng Regency during the Covid-19 pandemic. This study was conducted in a quantitative approach in the form of a correlational research, with 110 employees taken as research samples. The instruments used were questionnaires, interview guide, and employee performance appraisal forms which had been tested to determine their validation and reliability. Furthermore, the instruments were used to collect data by distributing questionnaires, interviews, and filling out employee performance appraisal forms. To answer the research problems, statistical tests and hypothesis testing were carried out. The descriptive statistics analysis and correlational statistics analysis (Spearman Rho) were used to answer the research questions. From the results of the study, it could be concluded that from the results of the Spearman Rho test the relationship between the quality of work life and the performance of employees at five-star hotels in the Lovina Beach tourist area is 0.123 which can be categorized very low. From the result of the coefficient of determination test, it was also found that the contribution of the quality of work life variable to the performance of employees is 0.04%, while the remaining contribution was influenced by other variable which was not examined in this study.